Red pitaya extract as natural antioxidant in pork patties with total replacement of animal fat. (January 2021) - Bellucci, Elisa Rafaela Bonadio; Munekata, Paulo E.S.; Pateiro, Mirian; Lorenzo, José M.; da Silva Barretto, Andrea Carla
Abstract: The antioxidant effects of red pitaya extract (PE) were evaluated in pork patties for 18 days at 2 °C. The following treatments were prepared: control (CON, without antioxidant), sodium erythorbate (ERY, 500 mg kg −1 ), PE low dose (PEL, 250 mg kg −1 ), PE medium dose (PEM, 500 mg kg −1 ), and PE high dose (PEH, 1000 mg kg −1 ). No significant effect was observed on chemical composition and cooking loss with the addition of PE, while a significant effect was noticed in cohesiveness ( P < 0.05). The intense pink colour of PE enhanced the colour stability during storage (9.33, 7.92 and 7.69 vs. 6.77 for PEH, PEM and PEL vs. CON, respectively; ( P < 0.05). TBARS (1.21 vs. 2.44 mg MDA/kg) and carbonyl values (5.45 vs. 6.87 nmol carbonyl/mg) of treated samples were lower than those observed in CON. Similar values were found between samples with PE and ERY. PE improved colour acceptance and the preference of pork patties. Therefore, PE is a very effective natural antioxidant by delaying colour and oxidative deterioration. Highlights: Red pitaya extract is a good ingredient to extend the shelf life of pork patties. Natural colorant to improve consumer acceptance of meat products. Dose-dependent effect of pitaya extract on antioxidant activity of pork patties Positive acceptance of pork patties with pitaya extract